Amino Acids as the Nitrogen Source to Synthesize Boron Nitride Quantum Dots for Fluorescence Turn‐off‐on Detection of Ascorbic Acid. Issue 13 (1st April 2020) - Kong, Yuelin; He, Yu; Zhou, Ji; Zhong, Shuhua; Song, Gongwu
Abstract: The BNQDs are synthesized by simple one‐step hydrothermal method, using amino acids as nitrogen source and boric acid as boron source. The BNQDs prepared by different amino acids emit strong blue fluorescence with the excitation wavelength from 280 to 400 nm. An "on‐off‐on" BNQDs fluorescent sensor is designed to detect ascorbic acid with Fe 3+ as medium, extending the application in sensing. The fluorescence of BNQDs is quenched by Fe 3+ on basis of the inner filter effect. With increasing of ascorbic acid, the fluorescence of BNQDs is recovered due to the oxidation‐reduction between Fe 3+ and ascorbic acid. The assay is capable of recognizing ascorbic acid in the concentration range of 1–100 μM with a detection limit of 0.0833 μM. In addition, the method has the potential to determine Fe 3+ and ascorbic acid in real water samples and human serum. Abstract : The BNQDs were prepared by amino acids as nitrogen source and boric boron source. In the presence of Fe 3+, the fluorescence of BNQDs was quenched due to the inner filter effect (IFE). After adding ascorbic acid, the fluorescence of BNQDs recovered on the basis of oxidation‐reduction. Therefore, a novel "on‐off‐on" fluorescence switch sensor was constructed to detect Fe 3+ and ascorbic acid synchronously.